Solve the factored quadratic equation (x-5) (x+3) = 0

1 answer

To solve the factored quadratic equation \((x-5)(x+3) = 0\), we can use the zero product property, which states that if the product of two factors is zero, then at least one of the factors must be zero.

We set each factor equal to zero:

  1. \(x - 5 = 0\)
  2. \(x + 3 = 0\)

Now, we solve each equation:

  1. For \(x - 5 = 0\): \[ x = 5 \]

  2. For \(x + 3 = 0\): \[ x = -3 \]

Thus, the solutions to the equation \((x-5)(x+3) = 0\) are: \[ x = 5 \quad \text{and} \quad x = -3 \]

Similar Questions
    1. answers icon 1 answer
    1. answers icon 1 answer
  1. 1)What method(s) would you choose to solve the equation:x2 + 2x - 6 = 0 A. Square roots; there is no x-term. B. Quadratic
    1. answers icon 1 answer
    1. answers icon 1 answer
more similar questions